A novel high precise laser 3D profile scanning method with flexible calibration. (September 2020) - Wu, Xiaojun; Tang, Na; Liu, Bo; Long, Zhili
Highlights: A line laser scanning method with high precise is presented in this paper. A new laser plane calibration device was designed and a ratio-cross invariant based laser plane calibration method was proposed to offer a flexible and high precise calibration result. An algorithm based on Hessian matrix and piecewise polynomial fitting is proposed to extract laser fringe center, and cubic spline interpolation algorithm is used to optimize the sub-pixel center to guarantee the measurement accuracy. Abstract: To improve the accuracy of laser-contour profile devices, we propose a 3D laser scanning system with high accuracy that includes camera and laser plane calibration, and laser-stripe center extraction. First, a calibration device was designed and manufactured, from which the fiducial points can be easily and accurately detected to calibrate the laser plane. Then through the perspective invariance and the projective invariant cross-ratio properties, a flexible and accurate calibration algorithm is presented. A polynomial fitting method is employed to overcome the discontinuity and thickness of the laser stripe center. Finally, a cubic spline interpolation is utilized to restore the continuous gray value of the transitional regions of the light stripe. Experimental results with different test pieces demonstrate that the minimum geometric accuracy is 18µm and the repeatability is less than  ± 3µm, which indicates that the proposed method is feasible to be used in industrial high precision measurement.